FAKTOR â FAKTOR YANG MEMPENGARUHI KEBERHASILAN PERTANIAN PADI SAWAH DI KENAGARIAN KAMBANG BARAT KECAMATAN LENGAYANGKABUPATEN PESISIR SELATAN - -, NIla - (STKIP PGRI Sumbar, 2014)
This research aims to know the factors that affect the success of the rice paddy field farming in the Western lengayang district kenagarian district kambang southern coast. Type of this research is a descriptive korelasional. The population in the study were all heads of family farmers who do a rice paddy field farming in the Western Lengayang District Kambang Kenagarian Pesisir Selatan, the profession as a peasant farmer families amounted to 756. Research samples taken with a proportional random sampling technique with a proportion of 10% so the sample amounted to 78 farmers rice. Results of this study found that: 1) there is a positive influence of irrigation rice field rice farming success against in kenagarian district lengayang district West kambang southern coast because t calculate > t table (2,611 > 1,665), the power of influence of the categories are (r = 0,0287), the magnitude of the contribution of irrigation to rice paddy farming success in Kenagariam District Lengayang District West Kambang South Coast including small 8.2%. 2) there was no influence of land management of the rice field agricultural success in the Kenagarian Subdistrict of West County Lengayang Kambang southern coast because t count < t table (0,088 1,665, strength < influence belongs to the category of weak (r = 0.01) and the magnitude of the contribution of 0.01% =. 3) there is a positive influence on the success of the capital between the rice paddy field farming in the Western Lengayang District Kenagarian District Kambang South F calculate > F table (2,741 > 2.73) power of effect including weak r = 0,187) and the magnitude of the contribution of 3.5%. 4) there is a positive influence of irrigation, land management and capital together-equal to the success of the rice farming of rice field in Kenagarian District Lengayang District West Kambang southern coast because F F > count table (2,925 > 2,73) power of effect including the categories are (r = 0,326), the magnitude of the contributions including substantial (10.6 percent).